A quasi three-dimensional visualization of unsteady wake flow in human undulatory swimming. (27th August 2019) - Shimojo, Hirofumi; Gonjo, Tomohiro; Sakakibara, Jun; Sengoku, Yasuo; Sanders, Ross; Takagi, Hideki
Abstract: Human undulatory underwater swimming (UUS) is an underwater propelling technique in competitive swimming and its propulsive mechanism is poorly understood. The purpose of this study was to visualize the three-dimensional (3D) flow field in the wake region during human UUS in a water flume. A national level male swimmer performed 41 UUS trials in a water flume. A motion capture system and stereo particle image velocimetry (PIV) equipment were used to investigate the 3D coordinates of the swimmer and 3D flow fields in the wake region. After one kick cycle was divided into eight phases, we conducted coordinate transformations and phase averaging method to construct quasi 3D flow fields. At the end of the downward kick, the lower limbs external rotations of the lower limbs were observed, and the feet approached towards each other. A strong downstream flow, i.e. a jet was observed in the wake region during the downward kick, and the paired vortex structure was accompanied by a jet. In the vortex structure, a cluster of vortices and a jet were generated in the wake during the downward kick, and the vortices were subsequently shed from the feet by the rotated leg motion. This suggested that the swimmer gained a thrust by creating vortices around the foot during the downward kick, which collided to form a jet. This paper describes, illustrates, and explains the propulsive mechanism of human UUS.